2012
DOI: 10.3109/08039488.2012.680910
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial on the effectiveness of long- and short-term psychotherapy on psychiatric symptoms and working ability during a 5-year follow-up

Abstract: Long-term psychotherapy is more effective than short-term therapy during a long follow-up, suggesting the need for a careful evaluation of suitability to short-term therapy. More research on the long-term effects of psychotherapy in large-scale studies is still needed, however.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 32 publications
0
28
1
2
Order By: Relevance
“…Maintenance of gains is reported from a number of controlled studies [3], but systematic information about true delayed effects (after treatment termination) is sparse [1,2]. In this clinical trial, 167 outpatients with mixed diagnoses were randomized to 20 or 80 weekly 90-min sessions of short- (STG) or long-term (LTG) group analytic therapy.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintenance of gains is reported from a number of controlled studies [3], but systematic information about true delayed effects (after treatment termination) is sparse [1,2]. In this clinical trial, 167 outpatients with mixed diagnoses were randomized to 20 or 80 weekly 90-min sessions of short- (STG) or long-term (LTG) group analytic therapy.…”
Section: Figmentioning
confidence: 99%
“…We have previously found that punitive and harsh self-introjects change more in LTG than STG [9]. Recent studies comparing psychodynamic therapies of different length and intensity indicated that long-term therapy was more favourable than short-term therapy with regard to depression and interpersonal functioning [2,3,8,10]. …”
Section: Figmentioning
confidence: 99%
“…Die Nachhaltigkeit wurde von den Autoren auf die deutlich stär-kere Therapiedosis zurückgeführt [10]. In einer RCT [11] konnte im Langzeitverlauf nach drei Jahren eine signifikant stärkere Reduktion der depressiven Symptomatik in einer psychodynamischen Langzeittherapie im Vergleich zu einer systemisch-lösungsorientierten Kurzzeittherapie gezeigt werden, während im Selbstrating nach drei und sieben Monaten nach Therapiebeginn signifikant stärkere Reduktionen sowie höhere Remissionsraten nach sieben bis zwölf Monaten bei systemisch-lösungsorien-tierter Kurzzeittherapie auftraten. Die Nachhaltigkeitseffekte der Dosis und therapeutischen Technik analytischer Psychotherapie konnten über die Beendigung der Therapie hinaus aktuell belegt werden [11].…”
Section: Längerfristige Stabilisierende Psychotherapie (Rezidivprophyunclassified
“…Es weist aufgrund des hohen Rückfallrisikos und des häufig rezidivierenden Verlaufs auf die Notwendigkeit als Erhaltungsthe-rapie und Rezidivprophylaxe hin und die Notwendigkeit der Aufklärung des Patienten über die Überlegenheit der Kombinationstherapie. Nachhaltige Effekte durch Psychotherapie sind bekannt und in Prozess-Ergebnis-Untersuchungen beschrieben worden [11].…”
Section: » Psychotherapie Ist Bei Allen Schweregraden Der Depression unclassified
“…Theoretically, the underlying model of psychopathology includes a range of different psychoanalytical theories such as ego psychology, object relations psychology, attachment theory, and self psychology Summers & Barber, 2010). Different psychodynamic psychotherapies can be of almost any length, ranging from a single or a few sessions (Abbass, Joffres, & Ogrodniczuk, 2009;Barkham, Shapiro, Hardy, & Rees, 1999) to fixed lengths such as 12, 16 or 24 sessions (Barber, Barrett, Gallop, Rynn, & Rickels, 2012;Leichsenring et al, 2013;Mann, 1973), and up to 2-3 times a week for several years (Knekt, Lindfors, Sares-Jäske, Virtala, & Härkänen, 2013). The activity of the therapist varies from highly active (as for example in Intensive Short-term Dynamic Psychotherapy; Abbass, Town, & Driessen, 2012;Davanloo, 2000) to significantly less active in classical Freudian psychoanalysis.…”
Section: Psychodynamic Therapymentioning
confidence: 99%